Characterization and quantification of different indigenous chicken production, feeding and management systems in Babati District - International Livestock Research Institute (International Livestock Research Institute, 2018)
This dataset is part of the focus on forages and feed as a key opportunity for driving sustainable intensification of crop livestock systems in Tanzania. It falls under integrated livestock feeds component (ILF) to enhance integration of improved management and feeding strategies with emphasis on utilization of local feed resources for indigenous poultry. The objective of the study was characterization and quantification of different indigenous chicken production, feeding and management systems in Babati District. To learn more about this dataset, please visit the ILRI Datasets Portal http://data.ilri.org/portal/dataset/baseline-dataset